KEDUDUKAN DAN PERAN ADVOKAT DALAM PROSES PENYELESAIAN PERKARA PIDANA - Achmad Rifai (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2008)
The position of advocates (lawyers) as a law advisors in any process of investigation must be central, in terms of that they must place themselves as the representatives of the suspect to get the an appropriate rights. It is mistaken that an advocate acts from the side of attorney as general prosecutor. In the course of law enforcement, it has been fairly set up either the roles of attorney representing the victim or the demanded person, the suspect. During the process of investigation, the investigator (attorney or police officer) is standing for the victim, nevertheless the suspects are represented by an advocate as their law advisor. In the level of prosecution, the victim must be put up with an attorney as the general prosecutor; the advocate, as the law advisor, represents the suspect.